2015
DOI: 10.1063/1.4919604
|View full text |Cite
|
Sign up to set email alerts
|

Shock wave convergence in water with parabolic wall boundaries

Abstract: The convergence of shock waves in water, where the cross section of the boundaries between which the shock wave propagates is either straight or parabolic, was studied. The shock wave was generated by underwater electrical explosions of planar Cu wire arrays using a high-current generator with a peak output current of $45 kA and rise time of $80 ns. The boundaries of the walls between which the shock wave propagates were symmetric along the z axis, which is defined by the direction of the exploding wires. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…While in this study, the concept of using parabolic wall boundaries was concluded from the contribution that they reduce the stress over the parabolic wall. A contribution also discussed that parabolic ships' hulls eliminate the turbulence of the water flow [17,24]. At the same time, a study of submerged parabolic obstacles showed a decrease in vortex sizes [23].…”
Section: Introductionmentioning
confidence: 98%
“…While in this study, the concept of using parabolic wall boundaries was concluded from the contribution that they reduce the stress over the parabolic wall. A contribution also discussed that parabolic ships' hulls eliminate the turbulence of the water flow [17,24]. At the same time, a study of submerged parabolic obstacles showed a decrease in vortex sizes [23].…”
Section: Introductionmentioning
confidence: 98%